Rule breaker investing : how to pick the best stocks of the future and build lasting wealth - Gardner, David, 1966- (Harriman House, 2025)
Want to know the real secret to investing success? It's not "buy low, sell high," picking "undervalued" stocks, or rebalancing winners... just as they start to win big. Those are old rules, often repeated-and often wrong. The secret is to break those rules! For over thirty years, David Gardner, the Motley Fool's Co-Founder and Chief Rule Breaker, has led millions of investors worldwide to market-beating returns through unconventional choices. His greatest stock picks have helped investors make 100+ times their money on companies including Amazon.com, Starbucks, Nvidia, Netflix, Booking Holdings, MercadoLibre, and Tesla. They look like obvious winners today, but to truly win big, you have to spot them before they're obvious. Now, for the first time, David shares his complete playbook, giving you everything you need to apply his proven process for yourself. Over eighteen engaging, practical chapters, you'll discover: How to adopt winning investing habits and behaviors. How to spot the best stocks of tomorrow, today. - How to build and manage a purpose-driven portfolio that reflects your best vision for our future. David's core message is clear: Everyone is an investor. With Rule Breaker Investing, you'll gain the tools, insights, and confidence to invest smarter, happier, and richer. Stop following the market. Start breaking the rules-and lead the way. Your financial future begins here.